Prawne i kryminologiczne aspekty zbrodni ludobójstwa serbskiej ludności na Bałkanach w XX wieku – wybrane zagadnienia - Ickiewicz-Sawicka, Magdalena (Elpis, 2014)
The text under the title Crime of Genocide Serbian population in the Balkans in the twentieth century, consists of three parts. The first one describes the theoretical concepts idea Genocide, the other contains reflections on war crimes, crimes against humanity, etc. - also on the basis of theoretical concepts. The third part of the article was presented to the Croatian concentration camp was set up to exterminate the Serbian civilian population into the territory of the Independent State of Croatia. Text close to the conclusions, which are all considerations the conclusion contained in the article.